2016
DOI: 10.1038/srep39258
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of microglia reveals signatures of cell activation and immune response, during experimental cerebral malaria

Abstract: Cerebral malaria is a pathology involving inflammation in the brain. There are many immune cell types activated during this process, but there is little information on the response of microglia, in this severe complication. We examined microglia by genome wide transcriptomic analysis in a model of experimental cerebral malaria (ECM), in which C57BL/6 mice are infected with Plasmodium berghei ANKA. Thousands of transcripts were differentially expressed in microglia at two different time points during infection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
(57 reference statements)
0
39
1
Order By: Relevance
“…Interferon-related microglia were also found in an Alzheimer's disease mouse model 13 and aged mouse brains 14 . INF-M and the previously identified interferon-related microglia 26 shared the expression of multiple interferonstimulated genes, although fewer members were identified in INF-M. IFN-M was not detected in spinal microglia at the same stage ( Fig. 2b).…”
Section: The Temporal Differentiation Of Cortical and Spinal Microglimentioning
confidence: 56%
“…Interferon-related microglia were also found in an Alzheimer's disease mouse model 13 and aged mouse brains 14 . INF-M and the previously identified interferon-related microglia 26 shared the expression of multiple interferonstimulated genes, although fewer members were identified in INF-M. IFN-M was not detected in spinal microglia at the same stage ( Fig. 2b).…”
Section: The Temporal Differentiation Of Cortical and Spinal Microglimentioning
confidence: 56%
“…In an animal model of cerebral malaria, microglial cells proliferated during the onset of the infection and showed upregulation of ‘genes involved in immune responses and chemokine production’ following the onset of cerebral malaria symptoms (Capuccini et al ., , p. 1). In vivo in mice it was shown that parasite‐specific CD8 + T cells interact with endothelial cells in an interferon‐gamma (IFN‐γ) dependent manner, and that this was responsible for activating endothelial cells in the brain microvasculature (Swanson et al ., ).…”
Section: Brain Infection By Protozoan Parasitesmentioning
confidence: 99%
“…Microgliosis is also a hallmark of experimental cerebral malaria. In this case, activated microglia were identified in the olfactory bulb and along the rostral migratory stream in the parenchyma, clustered near vessels with thrombi caused by infected erythrocytes (Capuccini et al ., ; Hoffmann et al ., ; Wilson et al ., ). In fatal cases of cerebral malaria caused by P. falciparum in English travelers, accumulations of microglia were observed around small veins in the brain parenchyma (Janota & Doshi, ).…”
Section: Microglial Reactions Against Parasitic Infectionsmentioning
confidence: 99%
“…In P. falciparum, the most virulent Plasmodium specie responsible for 90% of malaria mortality, attempts to directly knockout (KO) DPAP1 (Klemba et al 2004) or DPAP3 (Lehmann et al 2017) have been unsuccessful, suggesting that they are important for parasite replication. Also, in the P. berghei murine model of malaria, KO of DPAP1 or DPAP3 results in a significant decrease in parasite replication (Lin et al 2015;Capuccini et al 2016;Schwach et al 2015). DPAP1 localizes mainly in the digestive vacuole (Klemba et al 2004), an acidic organelle where degradation of haemoglobin takes place.…”
Section: Introductionmentioning
confidence: 99%